Magical urbanism : Latinos reinvent the US city / Mike Davis. - Davis, Mike, 1946- (The Haymarket series, 2001)
This account of the Latinisation of the american urban landscape explores questions such as, is the capital of Latin America a small island at the mouth of the Hudson River? and, Will Latinos reinvigorate the US Labout movement?